Evaluation of Halogenated Coumarins for Antimosquito Properties - Venugopala K. Narayanaswamy; Raquel M. Gleiser; Kabange Kasumbwe; Bandar E. Aldhubiab; Mahesh V. Attimarad; Bharti Odhav (The Scientific World Journal)
Mosquitoes are the major vectors of parasites and pathogens affecting humans and domestic animals. The widespread development of insecticide resistance and negative environmental effects of most synthetic compounds support an interest in finding and developing alternative products against mosquitoes. Natural coumarins and synthetic coumarin analogues are known for their several pharmacological properties, including being insecticidal. In the present study halogenated coumarins (3-mono/dibromo acetyl, 6-halogenated coumarin analogues) were screened for larvicidal, adulticidal, and repellent properties against Anopheles arabiensis, a zoophilic mosquito that is one of the dominant vectors of malaria in Africa. Five compounds exerted 100% larval mortality within 24 h of exposure. All coumarins and halogenated coumarins reversibly knocked down adult mosquitoes but did not kill them after 24 h of exposure. Repellent properties could not be evidenced. Five compounds were considered potential larvicidal agents for further research and development, while adulticidal activity was considered only mild to moderate.